Building green minds: Applying constructivist theory to cultivate reading interest in environmental issue - Adam, Andi (Journal of Environment and Sustainability Education, 2025)
Low reading interest among elementary students is a global concern that affects literacy development and academic performance. This study aimed to investigate how the application of constructivist learning theory, supported by environmental and cultural relevance, can enhance reading interest among fourth-grade students at Elementary School Unismuh Makassar. A Classroom Action Research (CAR) design was used, involving 30 fourth-grade students over two cycles. Each cycle followed the stages of planning, implementation, observation, and reflection. Data were gathered through observations, questionnaires, interviews, and documentation to assess changes in reading interest and comprehension.The implementation of constructivist-based strategies increased the percentage of students who read regularly from 40% to 70%. Participation in group discussions rose from 60% to 85%, and reading comprehension improved, with 80% of students demonstrating a solid grasp of the material. Contextual materials based on students' local environment and culture played a significant role in fostering motivation.This study contributes to the field of education by demonstrating that constructivist learning, when adapted to local contexts and supported by culturally relevant materials, can significantly improve reading interest and comprehension offering a replicable model for literacy enhancement in similar educational settings worldwide.